P584 Combining faecal calprotectin and sigmoidoscopy can predict mucosal healing in paediatric ulcerative colitis. (25th January 2019) - Park, S; Kang, Y; Koh, H; Kim, S
Abstract: Background: Treatment target of inflammatory bowel disease is evolving. Currently, mucosal healing (MH) is regarded as endoscopic treatment target and 'treat-to-target' strategy, which emphasises proactive assessment and optimising treatment, is commonly applied at the clinical setting. Although colonoscopies are essential for the strategy to be successful, there are some obstacles such as bowel preparation and using sedative drugs especially for paediatric patients. In this study, we tried to verify the usefulness of sigmoidoscopy, which is less invasive endoscopic procedure, combined with faecal calprotectin to assess MH. Methods: Total of 58 paediatric patients who are diagnosed with ulcerative colitis and followed up at Severance Children's Hospital from March 2015 to May 2018 were enrolled. Clinical data, laboratory findings including faecal calprotectin and endoscopic data were collected from the medical record. The predictive power of sMH (muscle healing of sigmoid colon and rectum) combined with faecal calprotectin to predict MH of entire colon was analysed. Results: Mean age of enrolled patients was 16.13 ± 2.88 years. Among 58 patients, 34 (58.6%) were females and 18 (31.0%) were in MH status. Median faecal calprotectin level was 486.5 μg/g. Faecal calprotectin cut-off value for the prediction of MH, identified by receiver-operating characteristic analyses, was 148 μg/g with an area under the curve of 0.808. Sensitivity, specificity, positive predictive value and negative predictive value of sMH in predicting MH were 1, 0.82, 0.72 and 1, respectively. When we combined sMH with faecal calprotectin less than cut-off value, sensitivity, specificity, positive predictive value and negative predictive value were 0.56, 1.0, 1.0 and 0.83, respectively. Conclusions: For patients with low-faecal calprotectin level, sigmoidoscopy might be sufficient enough to assess MH.